Complaint of Testicular Discomfort in Patient with Esophageal Adenocarcinoma - Kevin Krughoff; Alan Schned; Bing Ren; Vernon M. Pais (Case Reports in Urology)
We report a case of esophageal cancer with solitary metastasis to the testicle in a 71-year-old man. The tumor was picked up on physical exam following new onset complaints of pain and swelling. While most testicular masses in older men are due to lymphoma, this case highlights the need to consider metastatic disease as a source of new symptoms in patients with a recent cancer diagnosis.